2015
DOI: 10.1111/1346-8138.12882
|View full text |Cite
|
Sign up to set email alerts
|

Novel homozygous mutation, c.400C>T (p.Arg134*), in the PVRL1 gene underlies cleft lip/palate‐ectodermal dysplasia syndrome in an Asian patient

Abstract: Cleft lip/palate-ectodermal dysplasia syndrome is a rare, autosomal recessive disorder caused by homozygous loss-of-function mutations of the poliovirus receptor-like 1 (PVRL1) gene encoding nectin-1. Nectin-1 is a cell-cell adhesion molecule that is important for the initial step in the formation of adherens junctions and tight junctions; it is expressed in keratinocytes, neurons, and the developing face and palate. Clinical manifestations comprise a unique facial appearance with cleft lip/palate, ectodermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The affected subject belongs to a PPS family Peyrard-Janvid et al ( 2005 , 2014 ) KMT2D (MLL2) Kabuki syndrome type 1 (OMIM# 147920) Case report/series 1 CP HD Outside David-Paloyo et al ( 2014 ) MSX1 Wolf–Hirschhorn Syndrome (OMIM# 194190) Case report/series 1 CP OD Outside Only patient exhibiting a deletion on MSX1 gene, with a ring-chromosome. TA of 18, 38, 48 Nieminen et al ( 2003 ) OFD1 Orofaciodigital syndrome type 1 (OMIM# 311200) Family-based study 1 ARC OD Unclear Shimojima et al ( 2013 ) PVRL1 Cleft lip/palate-Ectodermal dysplasia syndrome (OMIM# 225060) Case report/series 1 CLP HP Unclear Yoshida et al ( 2015 ) SATB2 Glass syndrome (OMIM# 612313) Case report/series 1 CPO OD Outside Small intragenic duplication affecting SATB2 Lieden et al ( 2014 ) Glass syndrome (OMIM# 612313) Case report/series 2 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The affected subject belongs to a PPS family Peyrard-Janvid et al ( 2005 , 2014 ) KMT2D (MLL2) Kabuki syndrome type 1 (OMIM# 147920) Case report/series 1 CP HD Outside David-Paloyo et al ( 2014 ) MSX1 Wolf–Hirschhorn Syndrome (OMIM# 194190) Case report/series 1 CP OD Outside Only patient exhibiting a deletion on MSX1 gene, with a ring-chromosome. TA of 18, 38, 48 Nieminen et al ( 2003 ) OFD1 Orofaciodigital syndrome type 1 (OMIM# 311200) Family-based study 1 ARC OD Unclear Shimojima et al ( 2013 ) PVRL1 Cleft lip/palate-Ectodermal dysplasia syndrome (OMIM# 225060) Case report/series 1 CLP HP Unclear Yoshida et al ( 2015 ) SATB2 Glass syndrome (OMIM# 612313) Case report/series 1 CPO OD Outside Small intragenic duplication affecting SATB2 Lieden et al ( 2014 ) Glass syndrome (OMIM# 612313) Case report/series 2 …”
Section: Resultsmentioning
confidence: 99%
“…Zlotogora syndrome) (OMIM# 225060) as well as non-syndromic CL/P (EntrezGene; Suzuki et al 2000 ; Sözen et al 2001 ; Turhani et al 2005 ; Avila et al 2006 ; Scapoli et al 2006 ; Sözen et al 2009 ). So far, combined CL/P and HD has only been diagnosed in one CLPED patient who exhibited a homozygous nonsense mutation in the PVRL1 gene (Supplementary Table 4) (Yoshida et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a Japanese patient with CLPED was reported. 103 Nectin-1 encoded by the NECTIN1 gene is a Ca2 + -independent cell-cell adhesion molecule and is a crucial factor in adherens junctions and tight junctions. 102 CLPED1 shares several phenotypes with ED caused by TP63 mutations, and it has been shown that Nectin-1 and p63 are co-expressed in the epidermis and HF.…”
Section: Cleft Lip/palate-ectodermal Dysplasia Syndromementioning
confidence: 99%
“…Positional mapping and sequence analysis identified a novel, homozygous nonsense mutation (W185X) in NECTIN1 (Suzuki et al 2000). Further familial studies characterized additional variants (T324Yfs*65, G186Lfs*4, and R134X), plus others associated with nonsyndromic CL/P (Sozen et al 2001;Avila et al 2006;Aslar and Tastan 2014;Yoshida et al 2015) (Figure 3). Despite ample evidence suggesting Nectinmediated adhesion contributes to palate fusion, molecular redundancy and embryonic lethality have made modeling these human phenotypes difficult.…”
Section: Nectins and Afadinmentioning
confidence: 99%